PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KUE ULANG TAHUN SALTXSUCRE PONTIANAK - Sari Belvia; Wendy Suhendry; Emilia Farida Budi Handayani (FEB Universitas Sam Ratulangi Manado, 2023)
Abstract Saltxsucre is an online shop that sells birthday cakes. In Pontianak, there are quite a some of competitors who sell similar products online and offline. Product quality, price, and promotion are part of the strategy of business actors in increasing sales in order to survive. By implementing this strategy, it is hoped that it will have an impact on decision making to buy a Saltxsucre Pontianak birthday cake. This study aims to determine and analyze whether there is a significant effect between product quality, price, and promotion on the purchase decision of Saltxsucre Pontianak birthday cake. By using quantitative associative methods, this study used 40 Saltxsucre consumers who were determined to be a population by collecting data using a questionnaire using a google form. Sampling using simple random sampling method. The data obtained will be tested using the SPSS 25 program. The test is carried out using multiple linear regression analysis techniques. The test results show that the product quality and price variables have a significant effect on purchasing decisions. As for the Promotion variable, it has no significant effect on purchasing decisions. Keywords:Product Quality, Price, Promotion, and Purchase Decision.